Teknik Pemilihan Tanaman Cabai Unggul Mencapai Produktivitas Tinggi Dengan Fuzzy Multi Criteria Decision Making - Lubis, Adi Prijuna (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The chili plant is a plant that is generally widely cultivated in the territory of Indonesia, both in the highlands to the lowlands. Chili cultivation is a business opportunity for farmers to increase their income which is quite large. Chili is a plant that is classified as a vegetable and spice group that has an image of a spicy taste that evokes appetite. However, some farmers are still not maximally able to get increased production yields. The problem faced by farmers today is a failure in the yields that are not good enough. The process of selecting chili plants by farmers is still not optimal, lack of knowledge in determining chili plants. With a decision support system, it can help farmers to solve existing problems. Fuzzy Multi-Criteria Decision Making makes it easier for farmers to determine the alternatives and selected criteria, from the results of the analysis calculation to get the optimal value for the selected alternative, red chili plants A_2 get the highest integral value. A_2 The total value of the integral ∝ =0 (0.39063), ∝ =0,5 (0.54167), ∝ =1 (0.69271).